Pengaruh Waktu Inkubasi Pada Proses Sexing Sperma Berbasis Glutathione Terhadap Motilitas dan Membran Plasma Utuh Chilled Semen Domba Lokal - Annisaa Yusrina; Nurcholidah Solihati; Nena Hilmia (Jurnal Ilmu Ternak, 2018)
The aim of this study was to examine the effect of incubation time on sexing process based on glutathione to the motility and Intact Plasma Membrane (IPM) of chilled ram semen. The separation of X and Y sperm conducted by using BSA method. This research was experimental research using completely randomized design (CRD) with three treatment namely, 45 minutes (T1), 60 minutes (T2) and 75 minutes (T3). Data were analyzed using Anova followed by Duncan's multiple range test. Material used in this research was the fresh semen from ram with sperm motility ≥ 70% and 5 mM of glutathione. The result of this research showed that the highest percentage of motility in upper and bottom fraction belong to T1 (69,7% dan 68,8%), followed by T2 (66,4% dan 64,5%) and T3 (57,9% dan 57,6%).  In addition, the result of this research that the highest percentage of IPM in upper and bottom fraction belong to T1(75% dan 71,3%), followed by T2 (69,9% dan 68,4%) and  T3 (66,9% dan 65,5%). It can be concluded that the incubation time of 45 minute is the optimum time on sexing process based on glutathione so that the motility and IPM of chilled ram semen can be maintained.